The Midgut Muscle Network ofAnopheles aquasalis(Culicidae, Anophelinae): Microanatomy and Structural Modification After Blood Meal andPlasmodium vivax(Haemosporida, Plasmodiidae) Infection - Djane Clarys Baía-da-Silva; Alessandra S Orfanó; Rafael Nacif-Pimenta; Fabrício Freire de Melo; S.D.V. Simões; Iria Cabral; Marcus Lacerda; Maria das Graças Vale Barbosa Guerra; Wuelton Marcelo Monteiro; Nágila Francinete Costa Secundino; Paulo Filemon Paolucci Pimenta (2018)
The mosquito midgut is divided into two regions named anterior midgut (AMG) and posterior midgut (PMG). The midgut expands intensely after the blood ingestion to accommodate a large amount of ingested food. To efficiently support the bloodmeal-induced changes, the organization of the visceral muscle fibers has significant adjustments. This study describes the spatial organization of the Anopheles aquasalis (Culicidae, Anophelinae) midgut muscle network and morphological changes after bloodmeal ingestion and infection with Plasmodium vivax (Haemosporida, Plasmodiidae). The midgut muscle network is composed of two types of fibers: longitudinal and circular. The two types of muscle fibers are composed of thick and thin filaments, similar to myosin and actin, respectively. Invagination of sarcoplasm membrane forms the T-system tubules. Sarcoplasmic reticulum cisternae have been observed in association with these invaginations. At different times after the bloodmeal, the fibers in the AMG are not modified. A remarkable dilation characterizes the transitional area between the AMG and the PMG. In the PMG surface, after the completion of bloodmeal ingestion, the stretched muscle fibers became discontinued. At 72 h after bloodmeal digestion, it is possible to observe the presence of disorganized muscle fibers in the midgut regions. The Plasmodium oocyst development along the basal layer of the midgut does not have a significant role in the visceral musculature distribution. This study provides features of the visceral musculature at different blood feeding times of An. aquasalis and shows important changes in midgut topography including when the mosquitoes are infected with P. vivax.